OXYGEN CONSUMPTION AND ENERGY EXPENDITURE DURING AND AFTER STREET GAMES, ACTIVE VIDEO GAMES AND TV - Rauber,Suliane Beatriz (2018)
ABSTRACT Introduction: Physical activity has become less frequent since the 1980s, even among more active children. Objective: To analyze excess post-exercise oxygen consumption (EPOC) and total energy expenditure (TEE) in children during and after three different activities. Methods: Sixteen healthy children (9.6±0.1 yrs.) randomly underwent the following procedures lasting 30 minutes on different days: (a) traditional games (PLAY), (b) active video game (Dance Dance Revolution; DDR), and (c) watching television (TV). Oxygen consumption (VO2) was measured at rest, at the 10th, 20th, and 30th minute of intervention, and for 40 minutes post-intervention. TEE was also measured. Results: At the end of intervention, VO2 had increased by 330% and 166% for PLAY and DDR, respectively, compared to the rest. EPOC in PLAY was seen to occur at the 10th, 20th, and 30th post-interventional minutes from 7.00±1.02 (at rest) to 10.83±0.94, 10.03±0.58, and 9.80±0.77mL.kg-1.min-1, respectively. However, EPOC in DDR occurred at only the 10th postinterventional minute (7.04 to 8.61 mL.kg-1.min-1; p<0.01). After intervention, TEE in PLAY was greater than in DDR and TV (112.08±19.45 vs 56.98±6.34 vs 36.39±4.5 kcal; p<0.01), respectively. Conclusions: PLAY induced children to reach a greater VO2 during activity and greater EPOC and TEE compared to DDR and TV. Level of evidence A1b; Crossover study.